Awareness, acceptability and factors associated with newborn screening for sickle cell disease among pregnant women in a Northern Nigerian Tertiary Hospital - Aliyu, Rabi’at Muhammad; Adebiyi, Niyi Mustapha; Ibrahim, Yusuf Tabari; Halilu, Ibrahim; Waziri, Aliyu Dahiru; Abdulkadir, Isa; Ahmad, Hafsat Rufai (Frontiers in Hematology, 2026)
IntroductionSub-Saharan Africa has the highest burden of sickle cell disease (SCD), with less than 50% of affected children surviving beyond their fifth year. Nigeria is the most endemic country for SCD. Newborn screening (NBS) for SCD enables early diagnosis and enrollment in comprehensive management programs. However, NBS for SCD is not yet widely available in Nigeria. The success of NBS programs depends on awareness and acceptability among key stakeholders, such as pregnant women.ObjectivesThis study aims to determine the awareness and acceptability of NBS among pregnant women and to identify factors associated with their awareness and willingness to participate.MethodsA descriptive cross-sectional study was conducted among 210 attendees of the antenatal clinic at Ahmadu Bello University Teaching Hospital, Zaria. Data on socio-demographic characteristics, awareness, and acceptability of NBS were collected using an interviewer-administered structured questionnaire. Data were analyzed using SPSS version 21, with Fisher’s exact test used to assess associations between variables. A p-value of <0.05 was considered significant.ResultsThe mean age of participants was 28 ± 6.3 years. Most women (79.5%) were of Hausa ethnicity; 48.6% had tertiary education, 70.5% had a personal source of income, and 6.2% lived in rural areas. The majority of pregnant women (60.5%) were aware of NBS for SCD, and 96.7% were willing to have their babies undergo screening, mainly within the first 24 hours after birth (68.6%). However, more than two-thirds indicated they would need permission from their spouses to allow testing, even if the test were free of cost. Awareness of NBS for SCD was associated with younger age (<35 years), parity, educational level, socioeconomic status, tribe, and religion (p<0.05). Except for parity, these factors were also associated with willingness to accept NBS (p<0.05).ConclusionAwareness of NBS for SCD among pregnant women is high, with an even higher willingness to accept NBS. Most women prefer testing within 24 hours of birth but would need to seek spousal permission, even when the test is free of cost. Awareness and acceptability of NBS for SCD are associated with age, ethnicity, educational level, and place of residence.